In vitro induced pluripotency from urine-derived cells in porcine - Recchia, Kaiana; Machado, Lucas Simões; Botigelli, Ramon Cesar [UNESP]; Pieri, Naira Caroline Godoy; Barbosa, Gabriela; de Castro, Raquel Vasconcelos Guimarães; Marques, Mariana Groke; Pessôa, Laís Vicari de Figueiredo; Fantinato Neto, Paulo; Meirelles, Flávio Vieira; Souza, Aline Fernanda de; Martins, Simone Maria Massami Kitamura; et al. (Baishideng Publishing Group, 2022)
BACKGROUND The generation of induced pluripotent stem cells (iPSC) has been a game-changer in translational and regenerative medicine; however, their large-scale applicability is still hampered by the scarcity of accessible, safe, and reproducible protocols. The porcine model is a large biomedical model that enables translational applications, including gene editing, long term in vivo and offspring analysis; therefore, suitable for both medicine and animal production. AIM To reprogramme in vitro into pluripotency, and herein urine-derived cells (UDCs) were isolated from porcine urine. METHODS The UDCs were reprogrammed in vitro using human or murine octamer-binding transcription factor 4 (OCT4), SRY-box2 (SOX2), Kruppel-like factor 4 (KLF4), and C-MYC, and cultured with basic fibroblast growth factor (bFGF) supplementation. To characterize the putative porcine iPSCs three clonal lineages were submitted to immunocytochemistry for alkaline phosphatase (AP), OCT4, SOX2, NANOG, TRA1 81 and SSEA 1 detection. Endogenous transcripts related to the pluripotency (OCT4, SOX2 and NANOG) were analyzed via reverse transcription quantitative realtime polymerase chain reaction in different time points during the culture, and all three lineages formed embryoid bodies (EBs) when cultured in suspension without bFGF supplementation. RESULTS The UDCs were isolated from swine urine samples and when at passage 2 submitted to in vitro reprogramming. Colonies of putative iPSCs were obtained only from UDCs transduced with the murine factors (mOSKM), but not from human factors (hOSKM). Three clonal lineages were isolated and further cultured for at least 28 passages, all the lineages were positive for AP detection, the OCT4, SOX2, NANOG markers, albeit the immunocytochemical analysis also revealed heterogeneous phenotypic profiles among lineages and passages for NANOG and SSEA1, similar results were observed in the abundance of the endogenous transcripts related to pluripotent state. All the clonal lineages when cultured in suspension without bFGF were able to form EBs expressing ectoderm and mesoderm layers transcripts. CONCLUSION For the first time UDCs were isolated in the swine model and reprogrammed into a pluripotentlike state, enabling new numerous applications in both human or veterinary regenerative medicine.
Keywords: Induced pluripotent stem cells; Noninvasive; Pluripotency; Porcine; Reprogramming; Urine